Estimating far infrared surface emissivity over greenland from the tropospheric airborne fourier transform spectrometer (TAFTS) - Brindley,H; Murray,J; Bellisario,C; Harlow,C; Woolley,A; Fox,S; Last,A; Pickering,J (2016)
We report on efforts to obtain observationally based estimates of far-infrared surface emissivity over snow and ice. We highlight one flight from the CIRCCREX-COSMICS airborne campaign over Greenland during March 2015.